2023
DOI: 10.1111/acer.15026
|View full text |Cite
|
Sign up to set email alerts
|

Chronic ethanol exposure induces mitochondrial dysfunction and alters gene expression and metabolism in human cardiac spheroids

Abstract: Alcohol is the most consumed and highly addictive chemical substance, and chronic consumption of alcohol can lead to increased risk of health problems. According to the National Institute on Alcohol Abuse and Alcoholism, nearly one million people died from alcohol-related causes between 1999 and 2017, and in 2017 alcohol was involved with 2.6% of the ~2.8 million deaths in the United States (White et al., 2020). The impact of alcohol on human health is more prevalent on a global scale: in 2018, the World Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Understanding the molecular mechanisms underlying PAE-induced cardiotoxicity in human cells can help guide the development of management and therapeutic strategies for children affected by FASD and cardiac disease. Hwang et al investigated the effects of alcohol on mitochondrial features and transcriptomic and metabolomic profiles in cardiomyocytes derived from human induced pluripotent stem cells (hiPSC-CMs) [ 130 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the molecular mechanisms underlying PAE-induced cardiotoxicity in human cells can help guide the development of management and therapeutic strategies for children affected by FASD and cardiac disease. Hwang et al investigated the effects of alcohol on mitochondrial features and transcriptomic and metabolomic profiles in cardiomyocytes derived from human induced pluripotent stem cells (hiPSC-CMs) [ 130 ].…”
Section: Resultsmentioning
confidence: 99%
“…By modeling chronic alcohol exposure-induced cardiotoxicity in hiPSC-CMs, they showed that EtOH causes decreased mitochondrial membrane potential and mitochondrial content, decreased mitochondrial function, and altered expression of related genes [ 130 ]. EtOH also modified the glycolytic process and carbohydrate metabolic process as well as a reply to hypoxia, increased glycolysis, decreased mitochondrial function, and increased oxidative stress [ 130 ]. Therefore, an upregulation of T-cell chemotaxis has been shown as a potential causal link to proinflammatory response [ 130 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Harmful ethanol consumption is a trigger for more than 200 disease and injury conditions, which result in 3 million deaths every year representing 5.3% of all deaths worldwide 1 . During COVID-19 pandemic, the number of health problems related to ethanol consumption strikingly increased by 25% 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Formation of mtROS is regulated by a fine arrangement between mitochondrial biogenesis, dynamic (fusion and fission), recycle (mitophagy), and oxidative phosphorylation (OXPHOS) 15,16 . Ethanol induces mitochondrial dysregulation and/or mitochondrial-derived O 2 •- in alveolar macrophage 17,18 , heart, and T-cells 19,20 . Although the connection between mitochondria dysfunction and mtROS generation has been described in non-vascular cells, whether ethanol consume induces mitochondria dysfunction and subsequently ROS formation and vascular dysfunction is still unknown.…”
Section: Introductionmentioning
confidence: 99%